Performance of Nickel Foam (NF) Cathode in Microbial Electro-synthesis System for Generating Methane and Acetate Production from CO2 - Satar, Ibdal; Ahmed, Waled Abdo; Juwitaningtyas, Titisari; Syamsuddin, Arief; Majlan, Edy Haryanto; Bakar, Mimi Hani Abu; Kim, Byung Hong (Indonesian Journal of Environmental Management and Sustainability, 2025)
The cathode material is one of the key factors in enhancing the overall performance of microbial electrosynthesis system (MES). Nickel-based materials are the best option for cathodes in MES due to their excellent catalytic activity. This study aims to evaluate the performance of nickel foam (NF) as self-cathode material in MES for acetate production from CO2. A biocatalyst at the cathode was provided using a mixed-culture of anaerobic sludge from palm oil mill effluent (POME). The field emission scanning electron microscopy (FE-SEM) was used to analyze the cathode surface morphology, while high-performance liquid chromatography (HPLC) was used to quantify the volatile fatty acids (VFAs) in the effluent. The results indicate that the self-cathode NF exhibited excellent performance, achieving an acetate production rate (QAcetate) of 46.0 mM/d, compared to 41.7 mM/d with a graphite felt (GF) cathode at a cathode potential of -0.8 V. Additionally, the self-cathode NF in the MES system demonstrated a coulombic efficiency (CE) of approximately 22.9%. Moreover, the type of cathode material and the microbial community attached to the cathode surface significantly influenced MES performance.